Secondary Perforation Risk in Plate Osteosynthesis of Unstable Proximal Humerus Fractures: A Biomechanical Investigation of the Effect of Screw Length. Issue 12 (8th August 2019) - Ciric, Daniel; Mischler, Dominic; Qawasmi, Feras; Wenzel, Lisa; Richards, R. Geoff; Gueorguiev, Boyko; Windolf, Markus; Varga, Peter
ABSTRACT: Secondary perforation of screws into the joint surface is a commonly reported mechanical fixation failure mode in locked plating of proximal humerus fractures (PHF). This study investigated the influence that screws tip to joint distance (TJD) has on the biomechanical risk of secondary screw perforation and the stability of PHF. Ten pairs of cadaveric proximal humeri with a wide range of bone mineral density were used. Each specimen was osteotomized and instrumented with the PHILOS plate, simulating a highly unstable 3‐part fracture. Bones were randomized into a long screw group (LSG) with 4 mm TJD, or a short screw group (SSG) with 8 mm TJD. A custom biomechanical setup was used to test the samples to failure cyclically with a constant valley load and an increasing ramp. The number of cycles to the initial screw loosening event was significantly higher for the LSG (mean ± standard deviation: 17, 532 ± 6, 458) compared with the SSG (11, 102 ± 5, 440) ( p  < 0.01). The mode of failure during testing was lateral‐inferior displacement combined with varus collapse, with calcar screws perforating first. The number of cycles to failure event for LSG (27, 849 ± 5, 648) was not significantly different compared with SSG (28, 782 ± 7, 307) ( p  = 0.50). Screws that purchase closer to the joint had better initial stability and resistance against loosening. Placing longer screws, within limits dictated by the surgical guide, is expected to decrease the risk of secondary perforation failures in unstable PHF. These findings require clinical corroboration. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2625–2633, 2019